A intervenção ergonómica como dinâmica de aprendizagem: estudo de caso - Johann Petit (Universidade do Porto, 2008)
Starting from an ergonomic intervention for organizational redesign in a mutual health insurance company, in this paper our interest is in the learning of future "users of the organization". We develop a point of view according to which the ergonomic intervention can be designed to help future users learn about the future functioning of the organization. With this in mind, it is essential to involve future users in the organizational design. Following this direction, we propose to set the ergonomic intervention around "experimentation", with repeated tests on the planned organization, thus allowing the operators to participate in the choices and to test them.